2022
DOI: 10.3389/fphar.2021.798495
|View full text |Cite
|
Sign up to set email alerts
|

Role of Higenamine in Heart Diseases: A Mini-Review

Abstract: Higenamine, a natural product with multiple targets in heart diseases, is originally derived from Aconitum, which has been traditionally used in China for the treatment of heart disease, including heart failure, arrhythmia, bradycardia, cardiac ischemia/reperfusion injury, cardiac fibrosis, etc. This study is aimed to clarify the role of higenamine in heart diseases. Higenamine has effects on improving energy metabolism of cardiomyocytes, anti-cardiac fibroblast activation, anti-oxidative stress and anti-apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…179 The wide spectrum of roles of higenamine in heart diseases were reviewed thoroughly in 2022. 180 Inspired by the bioactivity reported for higenamine and to examine the traditional use of P. oleracea to treat asthma, our group hypothesized that some β 2 -ARs agonists may also exist within P. oleracea. Screening against a CHO-K1/GA15 cell line expressing β 2 -AR combined with a calcium assay, it was found that 68 and 50, together with 30, 56, 49, 64a, 54, 52, 31, 53, 55, and 51 (Table 2), were potent to moderate β 2 -AR agonists, whereas 63 and 148 were inactive.…”
Section: Marine Invertebratesmentioning
confidence: 99%
See 2 more Smart Citations
“…179 The wide spectrum of roles of higenamine in heart diseases were reviewed thoroughly in 2022. 180 Inspired by the bioactivity reported for higenamine and to examine the traditional use of P. oleracea to treat asthma, our group hypothesized that some β 2 -ARs agonists may also exist within P. oleracea. Screening against a CHO-K1/GA15 cell line expressing β 2 -AR combined with a calcium assay, it was found that 68 and 50, together with 30, 56, 49, 64a, 54, 52, 31, 53, 55, and 51 (Table 2), were potent to moderate β 2 -AR agonists, whereas 63 and 148 were inactive.…”
Section: Marine Invertebratesmentioning
confidence: 99%
“…72 was found to increase cardiac action potential and heart rate via β 1 -AR stimulation, while also preventing myocyte apoptosis and myocardial infarction through selective activation of the β 2 -AR/PI3K/AKT signaling pathway . The wide spectrum of roles of higenamine in heart diseases were reviewed thoroughly in 2022 …”
Section: Part V: Biological Activities Of Catecholamine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Higenamine, an active component of Aconitum carmichaeli , has shown a positive effect on improving chronic heart failure. Higenamine enhanced contractility of failing hearts and improved energy metabolism in cardiomyocytes, inhibited TGF-β1/Smad signaling transduction, thereby reducing cardiac fibrosis caused by cardiac fibroblast proliferation ( 45 , 46 ). The activation of the NF-κB increases the production of inflammatory cytokines and chemokines.…”
Section: Chinese Herbal Medicinal Ingredients For Warming and Tonifyi...mentioning
confidence: 99%
“…Aconite was widely used in ancient China to treat similar symptoms of heart failure (3). A previous study showed that the combination of water-soluble alkaloids of aconite and total ginsenosides had a therapeutic effect in a rat model of acute heart rats (4).…”
Section: Introductionmentioning
confidence: 99%